Mencari Jalan Tengah Penerapan Haluan Negara Dalam Sistem Perundang-Undangan Indonesia - Jufri, Muwaffiq; Safi', Safi'; Fahmi, Agung Ali; Mukhlis, Mukhlis (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2025)
The discuss about PPHN, it is closely related to its legal product, because the success or failure of the PPHN concept is very influential by what legal product is the basis for the rules. This research focuses on finding the ideal format for setting up PPHN in the Indonesian legal system. The formulation of the problem in this research are: First, what are the supporting and inhibiting factors for the implementation of PPHN in Indonesian laws and regulations?; Second, what is the ideal model for implementing PPHN in Indonesian laws and regulations? This study uses normative legal research which results in the conclusion that there are several potential supporters and obstacles in implementing this PPHN, both in the 1945 Constitution of the Republic of Indonesia, TAP MPR, and the legislative act. The ideal format for setting up the PPHN is through a legislative act based on the existence of the TAP MPR which specifically sets the boundaries of the direction of development (the direction of the state) as implicitly stated in the constitution. The affirmation of the boundaries of the direction of the country's direction is intended to ensure the achievement of the concept and direction of sustainable national development.